A novel maltooligosaccharide-forming amylase from Bacillus stearothermophilus. (August 2019) - Wang, Yinglan; Pan, Sihui; Jiang, Zihang; Liu, Siyu; Feng, Yan; Gu, Zhengbiao; Li, Caiming; Li, Zhaofeng
Abstract: A novel maltooligosaccharide-forming amylase (MFAse) from Bacillus stearothermophilus (Bst-MFAse) was heterologously expressed in B. subtilis and purified by hydrophobic and ion-exchange chromatographies. Bst-MFAse, an approximately 58 kDa monomer, could effectively hydrolyze linear α-glucan with DP > 6 and slightly hydrolyze maltohexaose. In addition, Bst-MFAse was proved to majorly produce maltopentaose and maltohexaose from starch and categorized as a maltopentaose-forming amylase. The action pattern was analyzed using amylopectin and amylose as substrate, showing that Bst-MFAse could rapidly reduce iodine blue value. Thus, Bst-MFAse was categorized as both a maltopentaose-forming amylase and an endo-amylase. During the initial period (2 h) of amylolysis, Bst-MFAse mainly cleaved amylopectin (18.7%) than amylose (14.0%). However, the final conversion rate (24 h) of amylose (68.8%) was slightly higher than that of amylopectin (64.8%). Bst-MFAse may have great potential applications in industry due to its highly specific activity, unique substrate specificity, and end-type product pattern. Highlights: A novel maltooligosaccharide-forming amylase (Bst-MFAse) was heterologously expressed and purified. Bst-MFAse showed a catalytic property significantly different from thermostable α-amylase. Bst-MFAse could effectively hydrolyze longer substrate, slightly hydrolyze maltohexaose but hardly hydrolyze maltopentaose. Bst-MFAse majorly followed an endo-type action pattern during starch hydrolysis. Amylopectin was a better substrate for Bst-MFAse, as compared with amylose.